Valorization of Bioresources for the Production of Polymer Using Lanthanide Borohydride as Catalysts - LOUGHMARI, Saliha; VISSEAUX, Marc; EL BOUADILI, Abdelaziz (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The use of natural materials derived from biomass or biodegradable polymer materials can be one of the solutions to be considered in reducing environmental pollution problems. In addition, some polymers have been shown to be biocompatible and thus beneficial in biomedical applications. Therefore, within the framework of this study, we will present the results of the application of lanthanide-borohydride systems (Nd(BH4)3(THF)3) combined with n-butylethyl magnesium in the block copolymerization of conjugated dienes (myrcene-styrene) and a conjugated diene with a polar monomer (L-lactide) for the synthesis of bio-sourced elastomers. The analysis of copolymers resulting from the copolymerization between myrcene and styrene shows that it is possible to insert up to 9.9% of styrene. Moreover, the stereoselectivity (1,4-trans) of the myrcene motif has not significantly changed, even in the presence of a significant amount of styrene in the reaction medium. The presence of the copolymer was confirmed by the observation of a peak at 146 ppm which corresponds to the ipso carbon of styrene.